An elastoplastic creping model for tissue manufacturing. (15th June 2019) - Pan, Kui; Das, Ratul; Phani, A. Srikantha; Green, Sheldon
Abstract: The manufacturing of low-density tissue paper involves a key process called creping, which consists of pressing and bonding a wet web onto a drying cylinder rotating at a high speed, and scraping it off subsequently. Creping is understood as a periodic debonding and buckling process which creates a series of micro-folds in the paper. Despite the fact that fibers in the web undergo significant plastic deformation during creping, previous models treat the web as a single thin elastic layer. In this paper we apply a particle dynamics model to investigate the effects of plasticity on creping. A bilinear elastoplastic material model with associated kinematic hardening rule is used to describe the constitutive behavior of the web and a discrete cohesive zone model is implemented for the interfacial delamination. Inclusion of the plasticity of the web leads to significant decrease in creping force and wavelength. A virtual tensile test is performed to predict the stretch and stiffness of the simulated tissue paper. It is found that the stretch increases and the stiffness decreases as the ratio between the creping amplitude and the wavelength increases, thus leading to a higher softness. The simulated tensile stress-strain curve shows significant nonlinearity and qualitatively agrees with experiments. Finally, we explore the "explosive bulk" regime by modeling the web as three individual layers connected by inter-layer bonds. A phase diagram for the creping regimes is constructed. Our simulations indicate that the "explosive bulk" is more likely to occur when the interfacial fracture energy is high and the cohesion of the web is weak.